2019
DOI: 10.1371/journal.pone.0217647
|View full text |Cite
|
Sign up to set email alerts
|

A novel YOLOv3-arch model for identifying cholelithiasis and classifying gallstones on CT images

Abstract: Locating diseases precisely from medical images, like ultrasonic and CT images, have been one of the most challenging problems in medical image analysis. In recent years, the vigorous development of deep learning models have greatly improved the accuracy in disease location on medical images. However, there are few artificial intelligent methods for identifying cholelithiasis and classifying gallstones on CT images, since no open source CT images dataset of cholelithiasis and gallstones is available for traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Different research studies and experiments on med-ical imaging were performed by the researchers using the ML approaches. Shenzhen, Pang et al (19) identified the cholelithiasis and classified the gallstone from CT scan images using YOLO model. Study results showed that consequently, the highest accuracy was achieved as 92.7% in identifying the granular gallstone in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different research studies and experiments on med-ical imaging were performed by the researchers using the ML approaches. Shenzhen, Pang et al (19) identified the cholelithiasis and classified the gallstone from CT scan images using YOLO model. Study results showed that consequently, the highest accuracy was achieved as 92.7% in identifying the granular gallstone in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Shanzen Pang et al (19) identified the cholelithiasis and classified the gallstone from CT scan images. They created their dataset by collecting 223846 CT scan images of 1369 patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deep learning has gradually become the mainstream in target detection after 2012 [ 15 ]. At present, many efficient target detection networks have been proposed and applied in the industrial field, such as yolo [ 16 19 ], Faster R-CNN [ 20 ], and NAS-FPN [ 21 ]. The yolo algorithm was proposed by Redmon et al After two years of development, it has grown from yolo to yolov3.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, YOLO was a convolutional network designed to detect and frame objects in an image. Subsequently, it was used to classify these objects and, then, segment the framing areas [37][38][39]. YOLO v3 [40] is extremely fast and treats the detection of the regions of interest as a regression problem by dividing the input image into a grid of size m × m, and for each cell in that grid it determines the probability that it belongs to a class of interest.…”
Section: Using Deep Cnnmentioning
confidence: 99%